Penerapan Digital Marketing melalui Media Sosial sebagai Upaya Memperluas dan Meningkatkan Pemasaran pada UMKM Keripik Tempe Assyifa' - Hafidhuddin, Muhammad Azam; Ikaningtyas, Maharani (Jurnal Bisnis Indonesia, 2024)
In the current era, SME players need to improve their marketing by implementing digital marketing sothat the products they sell can be known by the wider community. In marketing, Assyifa's Tempe ChipsSME is currently still marketing its products conventionally. The aim of this activity is to help partnersovercome their problems related to marketing which are still limited to conventional marketing. Themethods used to solve partner problems are socialization, training and mentoring. The digitalmarketing model used in this activity is the use of social media to reach more customers. The socialmedia used are Facebook and WhatsApp Business. This activity has an important role in helpingimprove marketing to partners. After the activities were carried out, SME players had anunderstanding of digital marketing using social media. SME players are able to manage and optimizeFacebook and WhatsApp Business accounts as media for conducting digital marketing. Throughdigital marketing as a marketing medium, SME players can market their products more widely andreach more consumers so that they have the potential to increase sales of these SMEs.Keywords: Digital Marketing; Social Media;SME